KERJASAMA UMAT BERAGAMA DALAM AL-QURâAN: PERSPEKTIF HERMENEUTIKA FARID ESACK - Soleh, A. Khudori (LP2M IAIN Mataram, 2010)
Hermeneutical method introduced by Farid Esack promotes a model of interpretation that combines texts and contexts. This means that interpretation begins from texts and is applied to contexts and then moves from contexts back to texts. It is thus a dialectical process where understanding of contexts should be confirmed to texts and the result of this process is used as a guideline of practice. This hermeneutic is grounded on some Qurâanic key words, such as taqwa, tauhid, al-nas, al-mustadlâafÃ»n fi al-ardh, âadl, qisth, and jihad, to avoid arbitrary interpretation of the Scripture. Applying Esackâs hermeneutic to interreligious relations, this study argues that interreligious cooperation between Muslims and non-Muslims is not forbidden but encouraged. This conclusion comes from the understanding of the verses pertaining to plurality of religions, religious affinities, and the story of Moses exodus and Israel children from Egypt. In these three examples, the Qurâan explicitly and implicitly gives respects and admits the truth of religions. Therefore, interreligious cooperation between Muslims and non-Muslims should be built up on this theological consciousness.